Reintegration of former Boko Haram members and combatants in Nigeria: an interpretative phenomenological analysis of community members' experiences of trauma. Issue 12 (2nd December 2022) - Ike, Tarela Juliet; Jidong, Dung Ezekiel; Ike, Mieyebi Lawrence; Francis, Christopher; Ayobi, Evangelyn Ebi
Abstract: Reintegration in conflict settings poses significant challenges. In Nigeria, while much emphasis is placed on deradicalising and rehabilitating former Boko Haram members, including combatants and their families, the community seems to receive minimal priority concerning the traumatic experience they face and its impact on limiting reintegration. This paper makes an original contribution by using an interpretative phenomenological analytical lens to explore community members who are victims with lived experiences of trauma in conflict settings. The study draws on semi-structured interviews with 30 participants recruited from Bornu, Adamawa and Kaduna states. Based on the analysed data, the study found that trauma limits reintegration and fuels scepticism about the genuine reform of the former Boko Haram members and combatants. Trauma was also perceived to transcend the immediate victims and extend to the community. We recommend a trauma-informed cognitive behavioural therapy intervention to create a positive outlook that encourages reintegration and reduces potential recidivism.